The process of agrarian reform in Chile: A critical analysis of the revolution - Alvear Ravanal, Julio (Derecho Público Iberoamericano, 2017)
The study approaches the process of Agrarian Reform in Chile from the legal and social point of view. Across the analysis in parallel of the origins politician partisan of the process, his impellers and the ideological contradictions of the reform, it raises how the juridical procedure were first forced, badly interpreted and finally changes of direction up to not being known by the same ones that had dictated them, in a process that is fitted inside the notion of “Revolution”